(untitled) (ALPHA. Journal of Arts, Literature and Philosophy, 2019)
This paper presents preliminary outcomes of the analysis of the rising tone phenomenon found in utterances with a wide focus produced by six monolingual Spanish speakers and six native speakers of Mapudungun who have a functional command of Spanish, all of them from Región de La Araucanía in Chile. The intonational phrases of the five first minutes of conversation with native speakers were analyzed in order to describe the pitch of nuclear and postnuclear syllables (tones). These were later compared with equivalent utterances produced by monolingual speakers. The outcomes, expressed in phonological notation (Sp-ToBI) and in semitones, show a tendency to a higher tone rise in speakers from the foothills of the Andes mountain range as compared with speakers from rural areas located nearer the capital of the Region